2017
DOI: 10.1242/jcs.202853
|View full text |Cite|
|
Sign up to set email alerts
|

Redox regulation of the yeast voltage-gated Ca2+ channel homolog Cch1p by glutathionylation of specific cysteine residues

Abstract: Cch1p, the yeast homolog of the pore-forming subunit α 1 of the mammalian voltage-gated Ca 2+ channel (VGCC), is located on the plasma membrane and mediates the redox-dependent influx of Ca 2+ . Cch1p is known to undergo both rapid activation (after oxidative stress and or a change to high pH) and slow activation (after ER stress and mating pheromone activation), but the mechanism of activation is not known. We demonstrate here that both the fast activation (exposure to pH 8-8.5 or treatment with H 2 O 2 ) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…One of the nine Cys residues in repeat II, Cys-798, is not conserved, even in yeasts and fungi, and was not subsequently examined. Note that the transmembrane topology model is completely identical to those of animal VGCCs and NALCNs and partly differs from the previously proposed model of Cch1, in which the four Cys residues in repeat I is located in the cytoplasm ( 27 ).…”
Section: Resultsmentioning
confidence: 64%
“…One of the nine Cys residues in repeat II, Cys-798, is not conserved, even in yeasts and fungi, and was not subsequently examined. Note that the transmembrane topology model is completely identical to those of animal VGCCs and NALCNs and partly differs from the previously proposed model of Cch1, in which the four Cys residues in repeat I is located in the cytoplasm ( 27 ).…”
Section: Resultsmentioning
confidence: 64%
“…Pichia pastoris E GSH roGFP1 [37,197] roGFP1-iE [37,197,198] roGFP1-iL [198] general redox state Redoxfluor [44] Saccharomyces cerevisiae E GSH rxYFP [31,43,46,[199][200][201] roGFP1 [25][26][27][28][29]202,203] roGFP2 [12,19,33,[204][205][206] roGFP [207] eroGFP [35,36,[38][39][40][41][42]208] Grx1-roGFP2 [15,24,32,47,48,[209][210][211][212][213][214] general redox state rxRFP [30] Redoxfluor [44,215] H 2 O 2 HyPer…”
Section: Fungimentioning
confidence: 99%
“…Several research groups conducted studies devoted to various transport proteins in microorganisms which turned out to be regulated by redox-sensitive mechanisms [43,209,211,258,263]. By recording E GSH using roGFP in catalases and peroxidases deprived S. Typhimurium after H 2 O 2 addition, van der Heijden et al discovered that at a potential of approximately −290 mV a switching point was observed after which the H 2 O 2 influx rapidly dropped to ~8% and ~3% of initial values in log-and stationary-phase bacteria, respectively [258].…”
Section: Redox Regulation Of Transport Proteins In Microorganismsmentioning
confidence: 99%
See 2 more Smart Citations